2011
DOI: 10.3892/or.2011.1448
|View full text |Cite
|
Sign up to set email alerts
|

A PVP-extract fungal protein of Omphalia lapideacens and its antitumor activity on human gastric tumors and normal cells

Abstract: Abstract. Omphalia lapidescens is an important medicinal fungus as well as traditional Chinese medicine used for disease treatment. It is mainly used as a vermifuge for anthelmintic therapy, but it has not been hitherto reported to possess antitumor activity. In this study, a purified bioactive protein in O. lapidescens (pPeOp) was obtained using polyvinylpyrrolidone (PVP) followed by gel filtration chromatography. To evaluate the in vitro antitumor activity of pPeOp in human gastric tumor cells (MC-4 and SGC-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 16 publications
1
10
0
Order By: Relevance
“…Furthermore, the results of the wound healing assay demonstrated that pPe O p decreased the migratory rate of MC-4 cells in a concentration-dependent manner. In addition, pPe O p had a marked lethal effect on MC-4 cells, which is consistent with Chen et al (14). However, the effect of pPe O p on cell migration was not investigated by Chen et al .…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Furthermore, the results of the wound healing assay demonstrated that pPe O p decreased the migratory rate of MC-4 cells in a concentration-dependent manner. In addition, pPe O p had a marked lethal effect on MC-4 cells, which is consistent with Chen et al (14). However, the effect of pPe O p on cell migration was not investigated by Chen et al .…”
Section: Discussionsupporting
confidence: 91%
“…The major constituent, pPe O p, was identified with relatively high chromatographic purity. pPe O p increased apoptosis in human gastric tumor cells compared with conventional Western treatments, which induce tumor cell (MC-4 and SGC-7901) death and apoptosis significantly, but also trigger minor apoptosis of normal gastric cells (MC-1) (14). To further understand the underlying molecular mechanisms of the antitumor activities of pPe O p, its effects on tumor cell migration and cell cycle progression were investigated.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The MC-4 and SGC-7901 cells were cultured as described in our previous study (38). The cultured cells collected at the stage of logarithmic growth were detached using 0.25% trypsin and their viabilities were shown to be >98%, as revealed using the Trypan blue exclusion test.…”
Section: Methodsmentioning
confidence: 99%